Complement factor I upregulates expression of matrix metalloproteinase‐13 and ‐2 and promotes invasion of cutaneous squamous carcinoma cells. Issue 11 (4th May 2021) - Rahmati Nezhad, Pegah; Riihilä, Pilvi; Piipponen, Minna; Kallajoki, Markku; Meri, Seppo; Nissinen, Liisa; Kähäri, Veli‐Matti
Abstract: The incidence of cutaneous squamous cell carcinoma (cSCC) is increasing globally. Here, we have studied the functional role of complement factor I (CFI) in the progression of cSCC. CFI was knocked down in cSCC cells, and RNA‐seq analysis was performed. Significant downregulation of genes in IPA biofunction categories Proliferation of cells and Growth of malignant tumor, in Gene Ontology (GO) terms Metallopeptidase activity and Extracellular matrix component, as well as Reactome Degradation of extracellular matrix was detected after CFI knockdown. Further analysis of the latter three networks, revealed downregulation of several genes coding for invasion‐associated matrix metalloproteinases (MMPs) after CFI knockdown. The downregulation of MMP‐13 and MMP‐2 was confirmed at mRNA, protein and tissue levels by qRT‐qPCR, Western blot and immunohistochemistry, respectively. Knockdown of CFI decreased the invasion of cSCC cells through type I collagen. Overexpression of CFI in cSCC cells resulted in enhanced production of MMP‐13 and MMP‐2 and increased invasion through type I collagen and Matrigel, and in increased ERK1/2 activation and cell proliferation. Altogether, these findings identify a novel mechanism of action of CFI in upregulation of MMP‐13 and MMP‐2 expression and cSCC invasion. These results identify CFI as a prospective molecular marker for invasion and metastasis of cSCC.